Aramaic Bowl Spells : Jewish Babylonian Aramaic Bowls Volume Two - Shaked, Shaul, (Magical and Religious Literature of Late Antiquity ;, 2022)
The corpus of Aramaic magic bowls from Sasanian Mesopotamia is perhaps the most important source we have for studying the everyday beliefs and practices of the Jewish, Christian, Mandaean, Manichaean, Zoroastrian and Pagan communities on the eve of the Islamic conquests. The bowls published in this volume are from the Schøyen Collection, which has over 650 texts in Jewish Babylonian Aramaic, Mandaic and Syriac, and forms the largest collection of its kind in the world. This volume presents editions of fifty-five Jewish Babylonian Aramaic texts, with accompanying introductions, translations, philological notes, photographs and indices. The themes covered are magical seals and signet-rings. It is the second in a multi-volume project that aims to publish the Schøyen Collection of magic bowls.